Peningkatan Keterampilan Siswa Memainkan Recorder Dengan Model Pembelajaran Langsung Di Kelas VI SD - Dini Novrania (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research aims to describe the planning and the improvement of the students’ skill in playing a recorder through the use of direct instruction model. this study was conducted in grade VI of elementary school Number 17 Gaduang, with a total number of 16 students as the research object. The result of the observation of the lesson plan in Cycle I show a percentage of 75%, and it increased to90% in Cycle II, and the observation on the Teacher’s aspect shows a percentage of 75% in Cycle I and it increased to 90% in Cycle II, While the students average score increased from 63,4 in Cycle I to 83.32 in Cycle II. Therefore it is concluded that the use of direct instruction model could improve the students skill in playing a recorder. Keyword: Student’s Skill, Recorder, Direct Instruction